Peer effects and educational achievement: Evidence of causal effectsusing age at school entry as exogenous variation for Peer quality - Isabel Pessoa de Arruda Raposo; Michela Barreto Camboim Gonçalves (EconomiA, 2020)
This paper evaluates the diffusion of peer effects on academic achievement of 4th grade students in the Brazilian public school system. Using data from Prova Brasil 2013, the identification strategy builds on the use of an IV approach, in which the instruments for peers' performance are the proportions of classmates born in the second semester of the year (and alternatively, in each quarter). The idea behind the instruments is that compulsory school enrolment laws generate variation in the child's age at school entry, which, in turn, make the date of birth within the year an important determinant of educational achievement and, at the same time, plausibly exogenous to the quality of the student's peers. The results demonstrate that classrooms with higher proportions of peers born in the 2nd semester (started school at a relatively older age) tend to perform better, on average, than those that concentrate children born in the 1st semester, even after the inclusion of a wide range of control variables. For the math and Portuguese language evaluations, a one standard deviation increase in the classmates' test scores improves individual achievement by 30% of a SD.
Keywords: I20; I21; C13; 330; Peer effects; Instrumental variables; School enrolment laws